2016
DOI: 10.1590/0074-02760160103
|View full text |Cite
|
Sign up to set email alerts
|

Nicotinamide mononucleotide adenylyltransferase of Trypanosoma cruzi (TcNMNAT): a cytosol protein target for serine kinases

Abstract: Nicotinamide/nicotinate adenine dinucleotide (NAD+/NaAD) performs essential functions in cell metabolism and energy production due to its redox properties. The nicotinamide/nicotinate mononucleotide adenylyltransferase (NMNAT, EC 2.7.7.1/18) enzyme catalyses the key step in the biosynthesis of NAD+. Previously, the enzyme NMNAT was identified in Trypanosoma cruzi (TcNMNAT), a pathogenic agent with epidemiological importance in Latin America. To continue with the functional characterisation of this enzyme, its … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 16 publications
0
3
0
3
Order By: Relevance
“…Cell lysis was performed following the previously described procedure. Purification of inclusion bodies using denaturing agents followed a previously reported method (Sánchez-Lancheros et al., 2016). In addition, purified samples were run in a preparative 16 × 19 cm 10% SDS-PAGE.…”
Section: Methodsmentioning
confidence: 99%
“…Cell lysis was performed following the previously described procedure. Purification of inclusion bodies using denaturing agents followed a previously reported method (Sánchez-Lancheros et al., 2016). In addition, purified samples were run in a preparative 16 × 19 cm 10% SDS-PAGE.…”
Section: Methodsmentioning
confidence: 99%
“…HsNMNAT-1 contains one serine residue (Ser136), which is a phosphorylation target of protein kinase C enzymes, and is involved in the regulation of the catalytic activity of the self-modified PARP1 enzyme [ 21 ]. It has recently been found that Trypanosoma cruzi NMNAT has one or more serine-phosphorylated residues [ 22 ], which are possibly necessary for its regulation. PfNMNAT may be regulated by phosphorylation in some of its residues.…”
Section: Resultsmentioning
confidence: 99%
“…En nuestro grupo de investigación se identificó que la síntesis del NAD + en T. cruzi ocurre en el citosol, catalizada por la única NMNAT del parásito 80,136 , y ello llevó a generar la hipótesis de que un eficiente sistema de distribución del dinucleótido existe en el parásito; por ende, en este trabajó se optó por estudiar a los candidatos a transportador del dinucleótido de T. cruzi TcNdt1, TcNdt2 y TcNdt3, identificados en un trabajo desarrollado anteriormente 142 . A continuación, se presenta el primer apartado correspondiente a la caracterización in silico de los 3 candidatos.…”
Section: Resultados Y Discusiónunclassified
“…Estudiar proteínas candidato a ser transportadores del NAD + en T. cruzi requiere de una aproximación en que se integren las particularidades de la biología del parásito, y el conocimiento construido acerca de los elementos que participan en el transporte de moléculas. Teniendo en cuenta que la homeóstasis del NAD + es vital, y que T. cruzi posee una única NMNAT citosólica 80,81 , debe existir un sistema de transporte que movilice esta molécula a lo largo de sus diferentes compartimentos subcelulares, sin embargo, hasta el momento este no ha sido identificado. De manera interesante, en otros organismos eucariotas se ha determinado que proteínas pertenecientes a la MCF son pieza clave de dichos sistemas 33,[49][50][51] .…”
Section: Preguntas De Investigaciónunclassified